Objective structured clinical examination, OSCEs: an advance in the teaching and learning process in the student's perception - Fabiana Aparecida Mayrink DE OLIVEIRA; Fernanda Ribeiro PORTO; Cleide Gisele RIBEIRO; Ana Estela HADDAD; Rodrigo Guerra DE OLIVEIRA; Antônio Márcio Lima FERRAZ JÚNIOR (Universidade Estadual Paulista, 2019)
Abstract Introduction The OSCE is a method of clinical competencies evaluation that has gained international popularity in medical and dental education. Objective The purpose of the present study was to describe the stages of development of the OSCE for the undergraduate course in Dentistry and to report the students' perception about this method of evaluation, regarding the degree of difficulty, time for each stage, importance of each station, number of stations, organization of the exam, as well as the total time for the OSCE. Material and method This research was an observational and cross-sectional study, composed of the carry out of an OSCE and later application of an evaluative questionnaire to the students who were in the fourth semester of the Dentistry course. These students had basic knowledge and an intermediate level of competences, compatible with their stage of education. Result As regards the number of stations, 43(97.7%) of the students responded that this was appropriate, OSCE process as a whole was very well organized (n=25; 56.8%), organized (n=17; 38.6%) or not very organized (n=1; 2.27%) and about the total time of the OSCE process, 29(65.9%) reported that it was appropriate; 10 (2.27%) said that it was short; 4 (9.09%), that it was long. Conclusion The student's perception was positive especially regarding to organization and the time attributed to each station. Furthermore, the students considered that the topics and questions applied in each station were relevant.